Kebijakan Islandia dalam Bidang Ketenagakerjaan sebagai Upaya Menanggulangi Kesenjangan Gender - Gek Diah Julya Pramuditha, Azzahra Arifiana Nawang Putri Hamida (Global and Policy Journal of International Relations, 2023)
Iceland, the first country with the lowest gender gap in the world raises questions about the regulatory system established by the Icelandic government. Judging from the condition of the community, the provision of equal rights and status to both women and men has been running effectively. A brief history in the past, women’s strike in 1975 seems to be one of the indicators in the making of a gendered environment in Iceland. This paper aims to find out about the regulations of the Icelandic government in dealing with gender gaps in the field of labor. This paper was written using descriptive qualitative methods and library study data collection. Several concepts such as women's movement and gender mainstreaming are being used in the making of this paper. The results of this study show that the fulfillment of women's labor rights in Iceland can be seen from the implementation of government policies, as well as providing space for women to advance in their careers.Keywords: Gender Equality, Women's Movement, Gender Mainstreaming, Labor.Islandia, negara dengan predikat kesenjangan gender paling rendah di urutan pertama di dunia memunculkan pertanyaan mengenai sistematika regulasi yang dibangun oleh pemerintah Islandia. Melihat dari kondisi masyarakatnya, pemberian hak dan status yang setara baik kepada perempuan maupun laki-laki berjalan secara efektif. Sejarah singkat di masa lalu, utamanya pada aksi mogok pekerja perempuan tahun 1975 tampaknya juga menjadi salah satu indikator terciptanya lingkungan gender sedemikian rupa di Islandia. Tulisan ini dibuat untuk mengetahui regulasi pemerintah Islandia dalam menangani kesenjangan gender khususnya dalam bidang ketenagakerjaan. Penelitian ini dibuat dengan menggunakan metode kualitatif deskriptif dan pengumpulan data studi kepustakaan. Adapun pembahasan dalam tulisan ini ditinjau dengan menggunakan beberapa konsep, yakni gerakan perempuan dan gender mainstreaming. Hasil dari penelitian ini yaitu terlihat pemenuhan hak ketenagakerjaan perempuan di Islandia yang dapat ditinjau dari implementasi kebijakan pemerintahan, serta pemberian ruang bagi perempuan untuk maju dalam berkarir.Kata Kunci: Kesetaraan Gender, Gerakan Perempuan, Gender Mainstreaming, Ketenagakerjaan. DOI: https://doi.org/10.33005/jgp.v11i01.3954